Phylogenetic position and taxonomic review of the Ianduba spiders (Araneae: Corinnidae) endemic to the Brazilian Atlantic rainforest - Fiorini de Magalhaes, Ivan Luiz (2016)
The spider genus Ianduba is known from seven species, all restricted to the Brazilian Atlantic rainforest, a biodiversity hotspot. The genitalic morphology of these spiders is rather peculiar and they have been considered incertae sedis in Corinnidae. We present novel morphological data for the genus, including scanning electronic microscopy images for several somatic and genitalic features, and test their phylogenetic position by including one Ianduba species in a large morphological matrix of dionychan spiders. Our results suggest that Ianduba is a true corinnid, possibly belonging in a clade sister to Corinninae. Furthermore, we here describe eight new species of the genus: I. acaraje sp.n. (Bahia), I. apururuca sp.n. (Minas Gerais to Espírito Santo), I. capixaba sp.n. (Espírito Santo), I. dabadu sp.n. (Espírito Santo), I. beaga sp.n. (Minas Gerais), I. benjori sp.n. (Rio de Janeiro), I. liberta sp.n. (Minas Gerais) and I. angeloi sp.n. (Minas Gerais to São Paulo). Six of the new species seem to be closely related to I. varia, previously considered an aberrant species. Thus, we divide the genus into two morphological groups. All species from the varia group (except for I. varia, which is synanthropic in southeastern Brazil) appear to be restricted, or more common, at altitudes of at least 800 m above sea level. We argue that unsampled montane rainforest areas from southeastern Brazil are likely to yield new records or even undescribed species of Ianduba, and that montane species are likely to be under threat of extinction. New records for previously known species are provided, the female of I. caxixe Bonaldo, 1997 is described and illustrated for the first time, and distribution maps and an identification key for the fifteen known species are provided.